The Role of the Halal Value Chain Process in MSMEs on the Economy of South Kalimantan - Malihah, Lola; Sauqi, Muhammad (MALIA: Jurnal Ekonomi Islam, 2024)
Introduction: The global halal industry has grown rapidly in recent years, providing great opportunities for business actors. Indonesia, with around 242 million Muslims, accounts for 11.7% of the world's Muslim population. To monitor the development of the halal industry, clear benchmarks are needed, such as the concept of a "halal value chain" that covers the production process from raw materials to final products. Method: This study aims to analyze the implementation of the halal value chain in MSMEs in South Kalimantan and its impact on regional economic development. The study was conducted in three main areas, Banjarmasin, Banjarbaru, and Banjar Regency with a total of 172 respondents from 58 MSMEs. A mixed method was used, namely a quantitative survey with a questionnaire and qualitative through interviews and observations. Result: The results showed that around 45% of MSMEs apply halal principles in production, while 73% have official halal certification. The main obstacles are the lack of understanding of the importance of halal certification, minimal supporting infrastructure, and limited access to certification bodies. As many as 68% of respondents stated that technical support from the government could help obtain halal certification. Conclusion and suggestion: The implementation of the halal value chain has the potential to increase the competitiveness of MSMEs, strengthen their position in the national market, and support local economic growth. These findings are expected to be the basis for local government policies in developing the halal industry for MSMEs.